Ecological Health Risk Evaluation of Potentially Toxic Metals in Saline Soils Used for Table Salt Production in Awe Salt Mining Community of Nasarawa State (Lafia Journal of Scientific and Industrial Research, 2026)
The assessment of potentially toxic metals (PTMs) in saline soils used for table salt production is critically important because salinity can enhance the solubility and transport of metals in soils. This study assessed the concentrations, contamination and ecological risks of selected PTMs in saline soils used for table salt production in Awe Salt Mining Community, Nasarawa State, Nigeria. Soil samples were collected and analyzed for metal (Al, As, Cr, Cd, Co, Cu, Fe, Hg, Mn, Ni, Pb, and Zn) concentration using Genius-IF energy dispersive X–ray fluorescence (EDXRF) spectrometer. Enrichment factor (EF), geo–accumulation index (Igeo), contamination factor (CF), degree of contamination (Cd), pollution load index (PLI) and ecological risk assessment (ERA) were evaluated using the measured concentrations of the PTMs. Result showed that Fe (37112.29±377.59–117044.29±993.20) was the most abundant metal. Elevated levels of Co, Cr, Cu, Fe, Hg, Mn, Pb and Zn in the investigated saline soils exceeding their respective average shale reference levels, were observed. EF values indicated that the investigated saline soils have very high enrichment of Co, Cr, Cu, Hg, Mn, Pb and Zn. CF values showed that Co, Cr, Cu, Hg, and Mn are probably responsible for the high contamination. Cd and PLI revealed high degree of contamination for all investigated saline soils. The presence Co, Cu and Hg may probably be the key controlling factor causing the potential ecological risk. These findings have provided valuable information for effective environmental management strategies and policy to alleviate the influence of PTMs generated from table salt mining environment.
Keywords: Heavy Metal; Ecological Risk; Soil Contamination; Table Salt Mining; Saline Soil